Moderating effect of management support on the relationship between HR practices and employee performance in Nigeria - Ismail, Abdussalaam Iyanda; Abdul Majid, Abdul Halim; Jibrin Bida, Mohammed; Joarder, Mohd Hasanur Raihan (SAGE Publications, 2019)
Given that management support and decisions do influence all the aspects of organization, this study investigates moderating effect of management support on the relationship between recruitment and selection, training and development, compensation, performance appraisal and succession planning and employee performance. The cross-sectional survey approach was used in which data were collected from 450 academics in the state-owned polytechnics in Nigeria. The partial least squares method (PLS) algorithm and bootstrapping techniques were used to test the study’s hypotheses. The results provided full support for four out of five hypothesized direct relationships. Likewise, the seventh and ninth hypotheses were supported. The overall findings signify that recruitment and selection, training and development, performance appraisal and succession planning are strong and positive predictors of employee performance, and management support is a moderator in training and development–employee performance relationship, and in compensation–employee performance connection. The result signifies that management support fortifies the effectiveness in the human resource practices–performance relationship. Limitation and suggestion for the future research are also discussed.